Energy-Dispersive X-ray Microanalysis of a Herbal Antimicrobial: Fifatrol - Reddy, K. Ramachandra (Asian Journal of Pharmaceutics (AJP), 2023)
Ayurveda is a natural system of medicine, which is acceptable worldwide now days. Most of the medications used in this traditional system belong to natural drugs derived from the plants and other natural resources. These naturally derived antimicrobial drugs are equally effective as the other synthetically designed drugs of other medicinal systems against the different microbes. A detailed compositional analysis of any drug is very necessary to establish its role. Energy-dispersive X-ray (EDX) or energy-dispersive spectroscopy is a kind of microanalysis of any elemental structure. It is based on the detection of characteristic X-rays generated under electron microscopy. It provides both quantitative as well as qualitative information in elemental analysis. It is very important and useful technique to study a new drug to understand the drug delivery as well as nanoparticles in composition of any drug. In the present study, we have used a plant based extract antimicrobial drug named Fifatrol for detailed compositional analysis by EDX microanalysis under scanning electron microscope to see the different proinflammatory and anti-inflammatory elements such as Ca, S, O, Na, and B.